Visible‐Light Induced C(sp2)−H Amidation with an Aryl–Alkyl σ‐Bond Relocation via Redox‐Neutral Radical–Polar Crossover. (20th October 2021) - Keum, Hyeyun; Jung, Hoimin; Jeong, Jiwoo; Kim, Dongwook; Chang, Sukbok
Abstract: We report an approach for the intramolecular C(sp 2 )−H amidation of N ‐acyloxyamides under photoredox conditions to produce δ ‐benzolactams with an aryl‐alkyl σ ‐bond relocation. Computational studies on the designed reductive single electron transfer strategy led us to identify N ‐[3, 5‐bis(trifluoromethyl)benzoyl] group as the most effective amidyl radical precursor. Upon the formation of an azaspirocyclic radical intermediate by the selective ipso ‐addition with outcompeting an ortho ‐attack, radical–polar crossover was then rationalized to lead to the rearomative ring‐expansion with preferential C−C bond migration. Abstract : Herein, a photocatalyzed, intramolecular C(sp 2 )−H amidation of N ‐benzoyloxyamides has been developed to afford δ ‐benzolactams with an aryl‐alkyl σ ‐bond relocation. Upon the formation of amidyl radical via reductive N−O bond cleavage, selective radical ipso ‐addition followed by a redox‐neutral radical–polar crossover was suggested to be responsible for the preferential C−C bond migration.